The Star of CPEC- Analyzing the hurdles to Gwadar’s Development - Dr. Umbreen Javaid, (Al-Qanṭara, 2023)
Ever since the launch of CPEC, Gwadar has gained extreme importance for Pakistan. The plans for it are marvelous but the journey from a small fishing town to a transnational shipping hub is long and riddled with obstacles. This research focuses on identifying the challenges, and their consequences and analyzing potential solutions. This qualitative research considers secondary data from a variety of research papers, articles, and official websites. This research concluded that most challenges to Gwadar’s development are born out of a communication gap between the federal government and the locals. The problem lies in the people of Balochistan – Gwadar in particular- not being involved in the policy design process. Furthermore, some challenges are a consequence of neglecting sustainability of different aspects of CPEC and the desperate need of contingencies. If the challenges discussed in this research aren’t dealt with effectively, they will be detrimental for the optimal working of Gwadar as the star of CPEC. To ensure that it is not the case, the CCI should be used effectively to reach mutual terms between the center and Balochistan and a timeframe needs to be implemented for development benefits to reach locals. It should be ensured that the interests of the locals don’t get buried under the international ones.